Mean propulsive velocity is a viable method for adjusting the resistance-training load at moderate altitude - Rodriguez-Zamora, L.; Padial, P.; Schoenfeld, B. J.; Feriche, B. (Frontiers in Sports and Active Living, 2019)
We examined the viability of using mean propulsive velocity (MPV) to adjust the load in the countermovement jump (CMJ) at moderate altitude. Twenty-four volunteers were assigned to a 4-week power-oriented resistance training (RT) program in either normoxia (N, 690 m) or intermittent hypobaric hypoxia (IH, 2,320 m). The load was adjusted to maintain execution velocity of CMJ at 1m·s-1 of MPV. Relative peak power output (Prel), and percentage of velocity loss throughout the sets (VL) were determined for each session. The internal load was measured by the rating of perceived exertion (RPE). The absolute load lifted was higher in IH compared to N (75.6 ± 8.4 vs. 58.5 ± 12.3 kg P < 0.001). However, similar relative increases for both groups were found when comparing the final values (IH: 8.2%, P = 0.007; N: 9.8%, P = 0.03) with no changes in VL between groups (P = 0.36). Post-study Prel improved significantly only in IH (+7% W·kg-1, P = 0.002). Mean RPE was greater in IH vs. N (6.8 ± 1.5 vs. 5.6 ± 2, P < 0.001). The MPV seems to be a viable method for adjusting external load during RT at moderate altitude. However, given that RT at moderate altitude increases RPE, it is prudent to monitor internal load when using the MPV to best determine the actual physiological stress of the session.